Pengaruh Current Ratio , Total Asset Turnover, Net Profit Margin Terhadap Perubahan Laba Pada Perusahaan Perdagangan Jasa dan Investasi yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017 - Rika Wani Juwita; Yois Nelsari Malau (Fakultas Ekonomi Universitas Kadiri, 2020)
The purpose of this study was to examine and analyze the effect of the current ratio, total asset turnover, net profit margin on changes in profits in the service trading and investment companies listed on the Indonesia Stock Exchange in the 2014-2017 period. The independent variables used in this study are, current ratio, total asset turnover, net profit margin while the dependent variable changes earnings. The population used in this study amounted to 134 companies by taking the financial statement data that is in the service trading and investment companies listed on the Indonesia Stock Exchange. The sample of this study was taken using purposive sampling obtained as many as 45 samples. This research uses a quantitative approach, descriptive research type, the nature of causal relationship research. Data collection techniques with documentation techniques. The statistical analysis test used is the classic asumi test, multiple linear analysis research model, and the coefficient of determination using the simultaneous test and partial test on the table of significant values of 0.05. The results of this study indicate partially the current ratio, total asset turnover, net profit margin does not have a positive and significant effect on changes in earnings, Simultaneously current ratio, total asset turnover, net profit margin influence and significantly affect earnings changes Adjusted R Square test results show 1.1% of the variation in the dependent variable changes in earnings that can be explained by the current ratio, total asset turnover, net profit margin while the remaining 98.9%.is explained by other variables that are outside this study for example company size, capital and devidensTujuan penelitian ini adalah untuk menguji dan menganalisis pengaruh current ratio, total asset turnover, net profit margin terhadap perubahan laba pada perusahaan perdagangan jasa dan investasi yang terdaftar di BEI periode 2014-2017. Variabel independen menggunakan current ratio, total asset turnover,net profit margin sedangkan variabel dependennya perubahan laba. Populasi berjumlah 134 perusahaan dengan mengambil data laporan keuangan pada perusahaan perdagangan jasa dan investasi yang terdaftar di BEI. Sampel penelitian menggunakan purposive sampling diperoleh sebanyak 45 sampel. Penelitian ini menggunakan pendekatan kuantitaif, jenis penelitian deskriptif, sifat penelitian hubungan kausal. Teknik pengumpulan data dengan teknik dokumentasi. Uji analisis statistik yang digunakan yaitu uji asumi klasik, model penelitian analisis linier berganda, dan koefisien determinasi menggunakan uji simultan dan uji parsial pada tabel nilai signifikan sebesar 0,05. Hasil penelitian secara parsial current ratio, total asset turnover,net profit margin tidak berpengaruh positif dan tidak signifikan terhadap perubahan laba. Secara simultan current ratio, total asset turnover,net profit margin berpengaruh dan signifikan terhadap perubahan laba Hasil uji Adjusted R Square menunjukkan 1,1% dari variasi variabel dependen perubahan laba yang dapat dijelaskan oleh current ratio, total asset turnover,net profit margin sedangkan sisanya 98,9% dijelaskan oleh variabel lain yaitu diluar penelitian ini contohnya ukuran perusahaan, modal dan deviden.